Rancang Bangun Sistem Informasi Penjualan Kura-Kura Berbasis Website Menggunakan Metode Prototype - Renaldi Wijaya Kusuma; Estu Sinduningrum (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Advances in information technology, especially the internet, have had a major impact on various fields, including the business world. The ease of access to technology encourages business people to utilize digital platforms, such as e-commerce, in operational activities. Turtle Cileungsi Store, a turtle sales business in the Bogor area, that the store still uses a manual system, namely the buyer must come to the Turtle Cileungsi store to search, select and purchase the desired turtle, sometimes the shop owner must first see the availability of turtle stock that the buyer will look for, thus making the buyer have to wait even longer. From these problems, a Kura-Kura sales system application is needed that can help deal with existing problems, such as preventing the loss of sales data, reducing errors in transactions, and facilitating direct sales access. To answer these problems, a web-based sales information system was designed and developed using the prototype method. This system was built using the PHP programming language and MySQL database. The implementation results show that the system is able to speed up the sales recording process, simplify report generation, and minimize data input errors. In addition, the system supports decision-making by providing more accurate and real-time information. With the implementation of this system, the management of store operations has become more efficient and effective, and has helped improve service quality and business productivity. Testing using the black-box testing method shows that all the main functions of the system run as expected. The test results from black-box testing show that there is a 20% increase in system efficiency, which indicates that system improvement and development is effective. With this test, the system can be more optimal, stable, and safe to use. Meanwhile, the test results with the System usability scale (SUS) obtained an average score of 80, which is included in the good category. Thus, it is expected that this system will be able to support the sales process more effectively, efficiently, and structured.